The first record of ascaridoidea eggs discovered in crocodyliformes hosts from the upper cretaceous of Brazil - Cardia, Daniel Fontana Ferreira [UNESP]; Bertini, Reinaldo J. [UNESP]; Camossi, Lucilene Granuzzio [UNESP]; Letizio, Luiz Antonio [UNESP] (Sociedade Brasileira de Paleontologia, 2018)
– A paleoparasitological investigation was carried out on Crocodyliformes coprolites discovered in the Municipality of Santo Anastácio, in the southwestern region of the State of São Paulo. Individual samples were extracted from the surface and internal portion of each coprolite which revealed the presence of thick-shelled parasite eggs in three of them. The morphological characteristics of the specimens, i.e., rounded or oval shape, thick-shelled with mammillated surface, as well as their size, suggest that these eggs belong to the superfamily Ascaridoidea, which are gastrointestinal parasite nematodes of vertebrates, popularly known as “roundworms”. This is the first record of Ascaridoidea eggs discovered in Crocodyliformes hosts from the Upper Cretaceous of Brazil.
Keywords: Ascaridoids; Bauru Group; Coprolites; Crocodylomorpha; Parasites